Cytological Effects of Two Varieties of Lathyrus Sativus L. Extracts on Onion Root Tip Cells (Journal of Bio-Science, 2023)
Lathyrus sativus L. causes lathyrism both in animals and human due to the presence of the neurotoxin β-ODAP (β -N-Oxalyl-L-α, β -diaminopropionic acid). This study was performed to find out the toxic effect of grass pea on onion root tip cells. The root lengths of onion were reduced as the concentrations of different plant parts extracts of grass pea increased. The percentages of chromosomal abnormalities, NV and ICV of onion root tip cells showed an increasing trend with the increasing of different extracts concentrations. The mitotic index and chromosomal abnormalities in treated onion root tip cells were significantly different than that of control. The mitotic index and chromosomal abnormalities had a reverse relationship. Almost all the treated root tip cells of onion showed this mito-depressive effect. From this findings, it may concluded that β -N-Oxayl-L- α, β-diaminopropionic acid (Lathyrogens) in Lathyrus sativus may be responsible for mitotic depression and chromosomal abnormalities on the root tip cells of onion.J. Bio-Sci. 31(1): 51-60, 2023